Legal Recognition of Indigenous Peoples in the Era of Social Transformation: A Constitutional and Customary Law Perspective - I Putu Endra Wijaya Negara; Deppa Ringgi (LEGAL BRIEF, 2026)
The existence of indigenous peoples within the Indonesian legal system has obtained strong constitutional recognition, as reflected in the 1945 Constitution, particularly Article 18B(2) and Article 28I(3), as well as statutory regulations such as Law No. 5 of 1960 on Basic Agrarian Principles and Constitutional Court Decision No. 35/PUU-X/2012. However, in the era of social transformation, legal recognition of indigenous peoples is not merely a normative issue but also a strategic concern in achieving social justice and sustainable legal development. This study employs a normative legal research approach, utilizing statutory, conceptual, and historical approaches, with data derived from library-based research. The findings reveal that the distinction between de jure and de facto recognition reflects a significant gap between state legal norms and the social realities experienced by indigenous communities. The study further identifies that the challenges of legal recognition are complex and multidimensional, encompassing normative, structural, social, and political dimensions. Therefore, harmonizing formal and factual recognition is essential to ensure substantive justice and legal certainty. Additionally, a comprehensive approach involving policy harmonization, institutional strengthening, and increased participation of indigenous peoples in regulatory processes is necessary to enhance the effectiveness of legal recognition in the context of ongoing social transformation.